Effectiveness of Cooperative Script Strategy in the Implementation of Character Education - Mohammad Zainuddin (Journal of Development Research, 2017)
Character education and development of Pancasila values need to be implemented ​​in schools to face globalization era that will bring many changes along with acceleration of new cultures and civilizations from various nations in the world. It means the world of education in generating quality of human resources and professionals must prepare a competitive generation of characters. A concrete steps to realize together is character education from an early age. On the other hand, the teacher as the spearhead in education world can insert character implementation in every learning process. One effective step that can be done is to implement cooperative script strategy in learning process and character implementation.